IMPLEMENTASI KEGIATAN ICE BREAKING DALAM MENINGKATKAN SEMANGAT BELAJAR SISWA SEKOLAH DASAR - Yulia, Sispa; Nurhayati; Zulmasri; Ardi Satrial (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Ice breaking is an activity implemented by everyone to attract attention and break the atmosphere in the room into its original state, namely an enthusiastic state. By implementing ice breaking, teachers are able to overcome boredom and saturation of students so that students' enthusiasm and enthusiasm are not lost during the learning process. This study aims to see how far the implementation of ice breaking activities can increase students' enthusiasm, interest and enthusiasm in learning. The method used in this study is a descriptive qualitative method with a qualitative approach, the subjects of this study were students and teachers of grade 3 SDN 09 Sirukam. The study was conducted using observation and interview techniques with teachers and students in elementary schools that became the object of research. The results of this study are that ice breaking activities are able to eliminate boredom, boredom and restore students' enthusiasm and interest in learning, in addition, this ice breaking also strengthens the emotional feelings of a teacher and student.